Newnes radio and RF engineering pocket book - Winder, Steve. (Newnes, 2002)
New material in the third edition includes mobile base station antennas, operation of cellular networks, SAW filters and ceramic resonators, modulation for stereo FM broadcasts, ADPCM, and vocoders. *The essential data and information for modern radio engineering at your fingertips *Based on the practical knowhow of practicing engineers *Ideal for reference and revision.